Glenohumeral internal rotation deficit measured in the coronal and the sagittal planes in baseball players - Inui, H.; Nobuhara, K. (Journal of Exercise, Sport & Orthopedics, 2016)
Baseball players exhibit more external rotation and less internal rotation at 90° of abduction in their throwing shoulders. Posterior capsular tightness is often regarded as a cause of Glenohumeral Internal Rotation Deficit (GIRD); however, it remains unclear whether posterior capsular tightness affects glenohumeral range of motion. The objective of this study was to clarify the relationship between posterior capsular tightness and GIRD. We evaluated 214 male baseball players with competitive levels at an average age of 18 ± 6 years during 5 years (2010 to 20114). Subjects were divided into four groups: 28 elementary school boys (age, 9-12 years), 57 high school boys (age, 13-15 years), 71 high school boys (age, 16-18 years), and 58 adult (15 professional and 43 amateur) players (age, 19-28 years). We measured the glenohumeral angles of horizontal abduction, adduction, internal and external rotation in the coronal and sagittal planes with 90° of abduction and compared the GIRD values in the two planes among the groups. Subjects were divided into two groups based on whether GIRD in the coronal plane exceeded 20° and angular values were also compared between the two groups. In 15 players, the posterior capsule was evaluated using arthrography. Angles of adduction on the throwing sides were smaller than those on the non-throwing sides and this tendency was apparent in players > 15 years of age. GIRD in the coronal plane showed no difference from that in the sagittal plane in each group. Subjects showing = 20° of GIRD in the coronal plane had lower GIRD values in the sagittal plane when the arm was horizontally adducted. Arthrography indicated that the posterior capsule was loose in the coronal plane even when the arm was internally rotated and that it stretched when the arm was horizontally adducted. GIRD in both planes indicated that posterior capsular tightness was not a cause of GIRD in the baseball players in our study